Comparison of three-dimensional reconstruction approaches for anthropometry in apparel design. Issue 11 (2nd November 2019) - Zhao, Yu; Mo, Yu; Sun, Mengqin; Zhu, Yi; Yang, Cong
Abstract: The anthropometry is the fundamental knowledge for apparel design. While quite a few techniques have been developed for this purpose, it also becomes an obstacle for conducting a customized apparel design. Not only because most of them are expensive but they are also not quite clarified in their accuracy, speed, implement, and complexity. This article investigates three existing anthropometric approaches including two-dimensional–three-dimensional (2D-3D) mapping, point-cloud approach, and dense-reconstruction approach. With conducting three experiments in terms of these approaches, 3D reconstructive model have been built and then used for anthropometry. The results in this study have addressed the aforementioned issues; in particular, the accuracy and reliability of the anthropometric measurements built on these three approaches have been clarified. There are two main contributions out from this study. The first one is the provision of several references for users or customers to select anthropometric approaches in different apparel design scenarios. The second one is the provision of the fundamental knowledge of anthropometry for the development of conducting a customized apparel design online.